Surveillance of avian malaria and related haemoparasites in common terns (Sterna hirundo) on the Atlantic coast of South America - Capasso, Sofía Carolina (2023)
Haemosporidia (Apicomplexa, Haemosporida) are protozoa that infect vertebrate blood cells and are transmitted by vectors. Among vertebrates, birds possess the greatest diversity of haemosporidia, historically placed in 3 genera: Haemoproteus, Leucocytozoon and Plasmodium, the causative agent of avian malaria. In South America, existing data on haemosporidia are spatially and temporally dispersed, so increased surveillance is needed to improve the determination and diagnosis of these parasites. During the non-breeding season in 2020 and 2021, 60 common terns (Sterna hirundo) were captured and bled as part of ongoing research on the population health of migratory birds on the Argentinian Atlantic coast. Blood samples and blood smears were obtained. Fifty-eight samples were screened for Plasmodium, Haemoproteus and Leucocytozoon, as well as for Babesia parasites by nested polymerase chain reaction and by microscopic examination of smears. Two positive samples for Plasmodium were found. The cytochrome b lineages detected in the present study are found for the first time, and are close to Plasmodium lineages found in other bird orders. The low prevalence (3.6%) of haemoparasites found in this research was similar to those reported for previous studies on seabirds, including Charadriiformes. Our findings provide new information about the distribution and prevalence of haemosporidian parasites from charadriiforms in the southernmost part of South America, which remains understudied.